A novel formula using energy contributions to calculate pure maximum rate of lactate production (P*La.max) during an all-out anaerobic cycling test - Kim, Y. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The aim of this study was to compare previous calculating formulas of maximal lactate produced rate (La.max) and a novel formula of pure La.max (PLa.max) during a 15-s maximal sprint cycling test (MSCT) and to analyse their correlations. METHODS: Thirty male national-level track cyclists participated in this study (n = 30). They performed a 15-s MSCT in which anaerobic power output (peak watt; Wpeak and mean watt; Wmean), peak and mean oxygen uptakes (V *O2peak and V *O2mean), and maximal blood lactate concentrations (Lamax) were measured. These variables were utilised for different calculations of *La.max and three energy contributions (phosphagen contribution; WPCr, glycolytic contribution; WGly, and oxidative contribution; WOxi). P*La.max calculation considered *La*, timespan until Wpeak (tPCr*peak), and contributed timespan of the oxidative system (tOxi). Other *La.max values without tOxi were calculated using decreased time by 3.5% from Wpeak (tPCr *3.5%) and tPCr*peak. RESULTS: Absolute (kJ) and relative (%) WPCr indicated higher levels compared to WGly and WOxi. Values of WGly in kJ and % were significantly higher than WOxi (p < 0.0001, respectively). The value of *La.max (tPCr *3.5%) was significantly higher than P*La.max and *La.max (tPCr*peak) (0.97 ± 0.18, 0.88 ± 0.13, and 0.85 ± 0.12, respectively; p < 0.0001) while *La.max (tPCr*peak) was lower than P*La.max (p < 0.0001, respectively). A very high association between P*La.max and *La.max (tPCr*peak) was observed (r = 0.99; R2 = 0.98). This was higher than the relationship between P*La.max and *La.max (tPCr *3.5%) (r = 0.87; R2 = 0.77). *La.max (tPCr*peak), P*La.max, and *La.max (tPCr *3.5%) correlated with absolute Wmean and WGly (vs. Wmean: r = 0.48, 0.45, and 0.43; vs. WGly: r = 0.73, 0.70, and 0.61, respectively). CONCLUSION: P*La.max as a novel calculation of *La.max provides more detailed insights into interindividual differences in energy and glycolytic demands than *La.max (tPCr*peak) and *La.max (tPCr *3.5%). In particular, because WOxi and WPCr can differ remarkably between elite cyclists, implementing those values in P*La.max can therefore establish more optimized individual responses for elite track cyclists.